Improving Science Learning Process and Outcomes in Elementary Schools Through Contextual Teaching & Learning - Fitriani, Fitriani; Krismanto, Wawan; Usman, Usman (Universitas Nahdatul Ulama Surabaya, 2023)
Science learning is a means for students to learn about the natural surroundings to develop an understanding of science concepts that are contextual to their daily lives. For this reason, this study aimed to examine the application of the contextual teaching & learning (CTL) to improve the process and learning outcomes of science learning in grade 5 UPT SD Negeri 287 Pinrang, South Sulawesi. The approach used is qualitative, with a class action research type. The results show that the CTL learning model learning process changes student learning activities, interactions, and teacher teaching activities. Changes in the learning process led to increased student learning outcomes. Teaching materials, learning media, and worksheets that are designed with contextual settings bring significant changes to student learning activities and have an impact on their better understanding. This study concludes that implementing the CTL learning model can improve the process and outcomes of science learning in grade 5 UPT SD Negeri 287 Pinrang, South Sulawesi.